Pemanfaatan media konseling online pada perguruan tinggi keagamaan islam negeri - Siregar, Risdawati; Pulungan, Muhammad Syukri (Institute for Advanced Science, Social, and Sustainable Future, 2024)
In order to enhance the professional competence of aspiring counselors enrolled in the Islamic Counseling Guidance Study Program, this research sought to disclose the online counseling model used at State Islamic Religious Universities. Interviews with the management of UIN Mahmud Yunus Batusangkar, UIN Sultan Syarif Kasim Riau, and UIN Sheikh Ali Hasan Ahmad Addary Padangsidimpuan's Islamic Counseling Guidance study program were used to gather research data. The findings demonstrate that, theoretically, Islamic Counseling Guidance and Islamic Education Counseling Guidance courses have been used to execute online counseling. This has made it easier to adapt to how information technology has developed. In actuality, though, online therapy is only done through social media platforms like Messenger, Instagram, WhatsApp, and Video Call. The study's findings indicate that in order to enhance the professional competence of Islamic Counseling Guidance students as potential Islamic counselors, managers of the Islamic Counseling Guidance Study Program and Islamic Education Counseling Guidance must create applications that are simple to use, particularly for guidance and counseling services.